PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTUAN EKSPERIMEN TERHADAP KETERAMPILAN PROSES SAINS - Jelita Panjaitan; Ika Trisni Simangunsong; Dede Parsaoran Damanik; Alpianis Hulu (Jurnal Darma Agung, 2020)
ABSTRACT This study aims at determining the significant effect of Team Assisted Individualization learning model with experimental assistance on science process skills on the subject matter of measurement in class X semester I of the Belawan Conscience High School Academic Year 2019/2020. This type of research is a quasi-experimental study to determine whether there is any influence or consequences of something caused by the subject, that is students. The population of this study is all students of class X semester I of SMA Belawan Conscience consisting of 4 classes. Class X-1 is as an Experiment class amounted to 25 people who were taught with the Team Assisted Individualization learning model assisted with experiments and Class X-3 as a control class amounted to 25 people who were taught by direct learning. The instruments in this study amounted to 8 items in the form of essays that have been tested for validity, reliability, difficulty level, and different power. From the results of the study, it was obtained that the sample came from a homogeneous population and was normally distributed. The research results obtained an average value of experimental pretest lower than the average value of the control class pretest. From the results of the two-party t test obtained t count < t table shows that the initial ability of the two classes is the same. Then given a different treatment and then held a post-test. After being tested, the average Team Assisted Individualization score is higher than the average value of Direct Instruction. The results of one-party t test results obtained t count > t table, this shows that there is a significant influence/effect on the use of the Team Assisted Individualization learning model assisted with experiments on science process skills in the subject matter of measurement in class X semester I of SMA Nurani Belawan Academic Year 2019/2020.